2014
DOI: 10.11138/ccmbm/2014.11.1.059
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Platelet Rich Plasma (PRP) in osseointegration of oral implants in dental panoramic radiography: texture based evaluation

Abstract: SummaryPurpose. In this study the temporal texture differentiation associated with the bone formation properties, around loaded oral implants after Platelet Rich Plasma (PRP) employment, was investigated in Panoramic Radiographs. Conclusion. This study provides evidences that PRP application may favor bone formation around loaded dental implants that could modify the dental treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…These growth factors have shown their potentials to stimulate cell proliferation and differentiation(Badran, Abdallah, Torres, & Tamimi, 2018). The current results are consistent with some clinical findings(Gentile, Bottini, Spallone, Curcio, & Cervelli, 2010;Georgakopoulos et al, 2014), which indicate further that local application of PRP has positive effects on peri-implant trabecular bone remodeling in dental implant surgery, such as increased the numbers of osteogenic cells and faster rate of bone maturation, while the PPP could sufficiently maintain bone width and height with no depression for the preservation of socket with buccal dehiscence(Hatakeyama, Marukawa, Takahashi, & Omura, 2014).TA B L E 2 The average concentration of platelets in whole blood, PPP, and PRP (mean and SD, ×10 9 /L) *, *** significant differences indicate, respectively, p < .005 and p < .0001 while comparing with whole blood samples. Abbreviations: PPP, platelet-poor plasma; PRP, platelet-rich plasma.…”
supporting
confidence: 91%
“…These growth factors have shown their potentials to stimulate cell proliferation and differentiation(Badran, Abdallah, Torres, & Tamimi, 2018). The current results are consistent with some clinical findings(Gentile, Bottini, Spallone, Curcio, & Cervelli, 2010;Georgakopoulos et al, 2014), which indicate further that local application of PRP has positive effects on peri-implant trabecular bone remodeling in dental implant surgery, such as increased the numbers of osteogenic cells and faster rate of bone maturation, while the PPP could sufficiently maintain bone width and height with no depression for the preservation of socket with buccal dehiscence(Hatakeyama, Marukawa, Takahashi, & Omura, 2014).TA B L E 2 The average concentration of platelets in whole blood, PPP, and PRP (mean and SD, ×10 9 /L) *, *** significant differences indicate, respectively, p < .005 and p < .0001 while comparing with whole blood samples. Abbreviations: PPP, platelet-poor plasma; PRP, platelet-rich plasma.…”
supporting
confidence: 91%
“…Only one study performed GBR (ArRejaie et al., ). PRP enhancing bone formation was found in two studies (ArRejaie et al., ; Georgakopoulos et al., ). This was associated with larger bone width, higher bone density and less marginal bone loss (ArRejaie et al., ; Georgakopoulos et al., ).…”
Section: Resultsmentioning
confidence: 93%
“… SFE (Table ): n = 12 (Bettega et al., ; Cabbar, Guler, Kurkcu, Iseri, & Sencift, ; Consolo, Zaffe, Bertoldi, & Ceccherelli, ; Del Fabbro, Corbella, Ceresoli, Ceci, & Taschieri, ; Kumar, Shaik, Nadella, & Chintapalli, ; Schaaf, Streckbein, Lendeckel, Heidinger, Rehmann, et al., ; Schaaf, Streckbein, Lendeckel, Heidinger, Gortz, et al., ; Stenport, Ortorp, & Thor, ; Thor, Sennerby, Hirsch, & Rasmusson, ; Thor, Wannfors, Sennerby, & Rasmusson, ; Torres et al., ; Wiltfang et al., ). Alveolar bone regeneration (Table and ): (a) Alveolar ridge preservation (Table ) n = 4 (Alissa, Esposito, Horner, & Oliver, ; Anitua et al., ; Farina, Bressan, Taut, Cucchi, & Trombelli, ; Mozzati et al., ). (b) Alveolar ridge augmentation (Table ) n = 2 (Eskan et al., ; Torres et al., ). Dental implants (Table ): n = 4 (ArRejaie, Al‐Harbi, Alagl, & Hassan, ; Georgakopoulos et al., ; Kundu & Rathee, ; Monov et al., ). …”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the addition of PRP may be beneficial since a significant positive effect occurred 43 . D'Aquino et al 44 performed autologous DPSC grafts in 7 patients (followed up for 1 year) who presented bone resorption in the second molar distal due to impacted inferior third molars.…”
Section: Therapies For the Regeneration Of Bone Tissuementioning
confidence: 75%